JAVA AND THE MAKING OP THE NATION - Soegijanto Padmo (Humaniora, 2000)
Java, one out of 13.000 islands in Indonesia, is the most densely populated island . Compared to those of outer islands, the soil of Java Island is the most fertile one . It is due to the availability of mountains which provide ash to the soil and the avilability of rivers which spread all over the island . This geographical condition is associated with the fact that Java was and is the centre of human activities or socio-economics . a s well as political and cultural dynamics not only in Indonesia but also in Southeast-Asia (The description of this chapter is based on the account of Ricklefs, 1981 ; Anwar Harjono, 1997 ; Aqib Suminto, 1985 ; Kuntowijoyo, 1991 ; Usman Tampubolon, 1991 : Deliar Noer, 1988 ; Korver, 1985 except exclusively stated) . The Dutch who come to Indonesia during trse period from the 17th until 18th century. did not make any significant change because they were basically to follow the activities of local traders, namely the Javanese . Madurese, Bugenese, as well as other Sumatranese who were actively sailing traditional sea-route connecting towns and cities located along coastal areas of the islands of Sumatra, Java, Smaller Islands (Sunda Kecil), South Kalimantan, Sulawesi and Maluku (Sartono Kartodirdjo, 1987 see also van Leur, 1955 ; Meilink-Roelotsz, 1962 ; Day, 1966 ; Furnivall, 1939) . In this period, Java seems to be the centre of not only political activities to the traditional rulers in Indonesia, although there were also traditional rulers in other Humaniora Volume Xll. No . 2/2000 islands such as in Makasar and East Sumatra, but also to the European powers namely the Dutch and British . s The degradation of local rulers in Java was marked by the penetration of interfOrence of military units of the Dutch . Through the implementation of the policy the so called to divide and rule (devide et i1nperaj, the Javanese people were exploited and impoverished . In the process of mobilization and exploitation of any resourdes available in the colony, local rulers were also used as mediators . Consequently the backwardness and poverty occuring in the colony was caused by the exploitation carried out by the colonizers as well by the condition of traditional socio-economic tructure. Apart from the basic human right based on Islamic teaching, the backwardness and the poverty existing in the majority of the people in Indonesia was the main issue raised by the innitiators of nationalist movement in the early period. In the process of the development of national awareness among many sectarian organizations there were many factors that could be associated with, namely the common suffering shouldered by the majority of the Indonesian people for so long period of time, the common interest namely the ultimate goal ©f obtaining independence from the colonizers, and the same in common in the territory as a basis in building a nation (Abdullah, 1966).